Lower Interferon Regulatory Factor-8 Expression in Peripheral Myeloid Cells Tracks With Adverse Central Nervous System Outcomes in Treated HIV Infection - D'Antoni, Michelle L.; Kallianpur, Kalpana J.; Premeaux, Thomas A.; Corley, Michael J.; Fujita, Tsuyoshi; Laws, Elizabeth I.; Ogata-Arakaki, Debra; Chow, Dominic C.; Khadka, Vedbar S.; Shikuma, Cecilia M.; Ndhlovu, Lishomwa C. (Frontiers in Immunology, 2019)
Cognitive dysfunction persists in 30–50% of chronically HIV-infected individuals despite combination antiretroviral therapy (ART). Although monocytes are implicated in poor cognitive performance, distinct biological mechanisms associated with cognitive dysfunction in HIV infection are unclear. We previously showed that a regulatory region of the interferon regulatory factor-8 (IRF8) gene is hyper-methylated in HIV-infected individuals with cognitive impairment compared to those with normal cognition. Here, we investigated IRF-8 protein expression and assessed relationships with multiple parameters associated with brain health. Intracellular IRF-8 expression was measured in cryopreserved peripheral blood mononuclear cells from chronically HIV-infected individuals on ART using flow cytometry. Neuropsychological performance was assessed by generating domain-specific standardized (NPZ) scores, with a global score defined by aggregating individual domain scores. Regional brain volumes were obtained by magnetic resonance imaging and soluble inflammatory factors were assessed by immunosorbent assays. Non-parametric analyses were conducted and statistical significance was defined as p < 0.05. Twenty aviremic (HIV RNA<50 copies/ml) participants, 84% male, median age 51 [interquartile range (IQR) 46, 55], median CD4 count 548 [439, 700] were evaluated. IRF-8 expression was highest in plasmacytoid dendritic cells (pDCs). Assessing cognitive function, lower IRF-8 density in classical monocytes significantly correlated with worse NPZ_learning memory (LM; rho = 0.556) and NPZ_working memory (WM; rho = 0.612) scores, in intermediate monocytes with worse NPZ_LM (rho = 0.532) scores, and in non-classical monocytes, lower IRF-8 correlated with worse global NPZ (rho = 0.646), NPZ_LM (rho = 0.536), NPZ_WM (rho = 0.647), and NPZ_executive function (rho = 0.605) scores. In myeloid DCs (mDCs) lower IRF-8 correlated with worse NPZ_WM (rho = 0.48) scores and in pDCs with worse NPZ_WM (rho = 0.561) scores. Declines in IRF-8 in classical monocytes significantly correlated with smaller hippocampal volume (rho = 0.573) and in intermediate and non-classical monocytes with smaller cerebral white matter volume (rho = 0.509 and rho = 0.473, respectively). IRF-8 density in DCs did not significantly correlate with brain volumes. Among biomarkers tested, higher soluble ICAM-1 levels significantly correlated with higher IRF-8 in all monocyte and DC subsets. These data may implicate IRF-8 as a novel transcription factor in the neuropathophysiology of brain abnormalities in treated HIV and serve as a potential therapeutic target to decrease the burden of cognitive dysfunction in this population.